Impact of Digital Engagement on Mental Health and Neuroplastic Changes in Adults - Das, Isha; Thomas, Augustine; Shrestha, Pushpa Lal (SXC Journal, 2025)
In the digital era, digital engagement has become an intrinsic part of daily life, particularly among young adults and professionals. However, the impact of screen usage on mental health and brain development remains understudied in Nepal. This study examines the relationship between screen time, psychological well-being, and neuroplasticity among adults in Kathmandu. Utilizing data from 359 participants aged 18 and above, we assessed psychological well-being using the WHO-5 Well-Being Index and evaluated maladaptive and adaptive neuroplasticity through self-reported digital behaviors. Regression analyses revealed that smartphone and social media usage had a weak negative correlation with psychological well-being (β = -0.267, p < 0.05; β = -0.244, p < 0.05) and weak to moderate positive correlation with maladaptive neuroplasticity (β = 0.342, p < 0.05; β = 0.411, p < 0.05). Conversely, engagement with educational content had a weak positive correlation with adaptive neuroplasticity (β = 0.215, p < 0.05), and work-related digital content was weakly negatively correlated with maladaptive neuroplasticity (β = -0.098, p < 0.05). Among students, excessive smartphone and social media use impaired cognitive development, whereas educational content and gaming had positive neurological effects. Among employed individuals, structured digital engagement (work-related tasks) mitigated the negative impact of screen time, whereas compulsive digital behaviors led to cognitive strain. While specific content promotes cognitive growth, habitual social media and excessive smartphone use may lead to detrimental emotional and neural outcomes. These findings show the importance of purposeful and balanced digital engagement to support mental health and cognitive resilience. Public health interventions should focus on digital literacy, mindful screen use, and promoting constructive content consumption to mitigate the adverse effects of excessive screen exposure.